Exciton Diffusion Lengths and Dissociation Rates in CsPbBr3 Nanocrystal–Fullerene Composites: Layer‐by‐Layer versus Blend Structures. Issue 8 (18th February 2019) - Yao, En‐Ping; Bohn, Bernhard J.; Tong, Yu; Huang, He; Polavarapu, Lakshminarayana; Feldmann, Jochen
Abstract: Solution‐processable perovskite nanocrystals (NCs) are gaining increasing interest in the field of photovoltaics because of their enhanced stability compared to their thin‐film counterparts. However, the charge transfer dynamics in perovskite NC based light‐harvesting systems are not well understood. By applying femtosecond differential transmission (DT) spectroscopy the photoinduced charge transfer from inorganic perovskite CsPbBr3 NCs to the fullerene derivative phenyl‐C61‐butyric acid methyl ester (PCBM) is investigated for two fundamentally different architectures, namely layer‐by‐layer heterostructures and blend structures. By varying the thickness of the NC layer on top of the PCBM in the layer‐by‐layer heterostructure, an exciton diffusion length of 290 ± 28 nm for CsPbBr3 NC is extracted. The diffusion process is followed by an ultrafast exciton dissociation (within 200 fs) at the CsPbBr3 NC/PCBM interface. In blend structures an overall faster charge transfer process is observed. Furthermore, photoconductivity measurements on a blend structure‐based photodetector reveal an effective charge extraction from the active layer resulting in a high photosensitivity. DT measurements on this blend structure including adjacent electron‐ or hole‐transport layers give insight into the extraction process and suggest a certain degree of phase segregation, which assists the charge collection. Abstract : The exciton dynamics in CsPbBr3 nanocrystals adjacent to fullerene electron acceptors is systematically investigated for layer‐by‐layer and blend structures. For both of these nanocrystal–fullerene composites the exciton diffusion lengths and dissociation rates are experimentally determined. This study provides fundamental knowledge on the charge transfer and extraction processes in these systems. These are key properties that control the performance of optoelectronic devices.